From Central Africa to the World: A Review of Monkeypox’s Spread, Symptoms, and Current Treatment Approaches - Singh, Ujjawal; Sharma, Ramsha; Kamal, Raj; Diksha; Paul, Priyanka; Kumar, Ranjeet (Anti-Infective Agents, 2026)
IntroductionMpox is a zoonotic disease caused by the Mpox virus, an Orthopoxvirus primarily infecting small mammals. Historically endemic to Central and West Africa, Mpox has emerged globally in recent years, likely linked to the cessation of smallpox vaccination programs. This review aims to provide a comprehensive synthesis of current knowledge on Mpox, focusing on its molecular biology, epidemiological trends, and therapeutic strategies to address recent global outbreaks.MethodsThe review integrates data from recent case studies, epidemiological reports, and clinical trials to examine the virus's genetic diversity, modes of transmission, and global spread. Additionally, it explores the efficacy and accessibility of vaccines and antiviral treatments, with particular attention to challenges in low-resource settings.Results and DiscussionAnalysis highlights the global Mpox outbreak from 2022 to 2023, during which 1,285 confirmed cases across 28 non-endemic countries were reported. This outbreak emphasizes the virus's capacity for global spread, its clinical manifestations, and the effectiveness of available treatment options. The review also identifies gaps in understanding Mpox’s genetic evolution and treatment scalability.ConclusionThis review underscores the critical need for further research into Mpox's transmission mechanisms, genetic evolution, and therapeutic approaches. Addressing challenges related to vaccine distribution and antiviral access, particularly in low-resource settings, is essential for managing future outbreaks effectively.
Keywords: congo basin